eNd Points Challenges for Science and Policy - Johan Sliggers (The Scientific World Journal)
The theme of this Second International Nitrogen Conference is “Optimising nitrogen management in food and energy production and environmental protection”. With this theme in mind and with some observations, partly made during the week of the conference, some remarks can be made that will hopefully contribute to the goal of this conference and challenge and inspire both scientists and policy makers. Although being a representative of the Dutch government, the views and ideas brought forward in this paper do not necessarily represent those of the Dutch government. Also be aware of the fact that the ideas presented here are very much the views of a policy maker from a Western developed country.